2021
DOI: 10.1002/jcla.24014
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte to high‐density lipoprotein cholesterol ratio as an independent risk factor for papillary thyroid carcinoma

Abstract: Background Papillary thyroid carcinoma (PTC) is considered to be an inflammatory disease. This study aimed to investigate the association of monocyte to high‐density lipoprotein cholesterol ratio (MHR) with PTC. Methods Clinical parameters from 300 patients with PTC and 552 patients with benign thyroid nodule were compared. Serum renal function and liver enzymes, fasting plasma glucose, lipid profile, and blood cell count were measured. Results Patients with PTC had a higher MONO (p < 0.001) and MHR (p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
4
7
0
Order By: Relevance
“…Corroborating our study, the three cohort studies all showed an association between a lower level of HDL-C and a higher risk of thyroid cancer [8,11,29]. Among the cross-sectional or case-control studies, a lower level of HDL-C was reported among cases of thyroid cancer, compared to controls, in four studies [10,18,20,21], although not all differences were statistically significant. However, no difference was noted between cases and controls in the other five studies [13,15,22,24,25].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Corroborating our study, the three cohort studies all showed an association between a lower level of HDL-C and a higher risk of thyroid cancer [8,11,29]. Among the cross-sectional or case-control studies, a lower level of HDL-C was reported among cases of thyroid cancer, compared to controls, in four studies [10,18,20,21], although not all differences were statistically significant. However, no difference was noted between cases and controls in the other five studies [13,15,22,24,25].…”
Section: Discussionsupporting
confidence: 71%
“…The cohort study did not find a statistically significant association between per quintile increase in TC and risk of thyroid cancer among either men or women [17]. Among the cross-sectional or case-control studies, six reported a lower level of TC [14,18,20,21,24,25], whereas three reported a similar or higher level of TC [16,22,26] among cases with thyroid cancer, compared to controls. Some of the studies [18,22,25,26] were relatively small, making random finding a potential concern.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, there are few studies exploring the function of MHR in thyroid disorders. Recently, several reports have declared that MHR is closely linked to papillary thyroid carcinoma as well as thyroid nodule [25,26] . So far, no reports on the correlation between MHR and TAO have been published.…”
Section: Discussionmentioning
confidence: 99%